Growth, powdery mildew severity and yield of green beans in response to potassium sources - Gaion, Lucas Aparecido; Menezes, Davi Cristian Del Hoyo; Reis, Aline Dell Passo; Tonini, Mariana Mota; Nascimento, Nilton Carlos Gonçalves; Repetti, Cláudia Sampaio Fonseca (Revista de Ciências Agroveterinárias, 2023)
Brazil has faced serious problems with the supply of potassium fertilizers in recent years. This has caused prices to rise and even shortages of the main potassium fertilizer used by producers, potassium chloride. Therefore, the objective of the present work was to evaluate a national potassium silicate (K6) as an alternative source to the use of potassium chloride for the green beans crop. For this purpose, green beans seeds cv. Macarrão Rasteiro were sown in the field at a spacing of 0.50 x 0.20 m. A randomized block design with four treatments and five replications was used. The treatments were constituted as follows: (i) control – without potassium fertilization; (ii) potassium chloride; (iii) potassium silicate - K6; (iv) 50% potassium chloride + 50% K6. Fertilizers were applied at the time of sowing and doses were determined based on soil analysis and recommendations for the crop. Plant height, shoot fresh and dry mass, pod fresh and dry mass, yield estimation and occurrence of powdery mildew were evaluated through severity scores. It was found that in terms of plant growth, there was no influence of potassium fertilization on plant growth. In addition, pod productivity showed a reduction throughout the evaluation period and little influence of fertilization. However, total pod productivity was higher in plants that received K6 compared to plants fertilized with potassium chloride. The application of K6 also contributed to the reduction of powdery mildew severity. Thus, we conclude that K6 is a viable source of potassium in substitution of potassium chloride for the green beans.